The social and economy elements influencing the aging workers contribution: case in private universities, Selangor Malaysia - Uma Murthy; Norehan Abdullah; Hussin Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this research paper is to explore the social and economy elements among private universities aging workers to continue working. There are four variables were studies which are work-life balance, working experience, financial issues and working environment. The targeted populations was aging workers 55 to 60 years working in private education industries in Selangor, Malaysia. A questioners was distributed among 200 aging workers. Data was collected using a probabilities sampling methods, particularly a stratified random sampling technique. The findings indicate that work-life balance, working experience, financial issues and working environment contribute in the participation of aging workers in Malaysia.